Green IT empowerment, social capital, creativity and innovation: A case study of creative city, Bantul, Yogyakarta, Indonesia - Muafi (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This study aims at analyzing the role of empowerment of Green IT in SMEs and social capital of the creativity and innovation of creative SMEs in Bantul, Yogyakarta, Indonesia. Design/methodology/approach: A statistical technique used in the present study was Partial Least Square. The primary data of the present research were obtained from questionnaires and interviews with some respondents. While secondary data were gained through the records and publications of related instancies. Findings: The research concluded that the empowerment of Green IT provides a significant role in creativity and innovation as well as social capital, and at the same time it also supplies a significant role in innovation. Research limitations/implications:. This study is proposed to fill the research gap and at the same time to emphasize the importance of the creative empowerment of SMEs in Indonesia in adopting Green IT and that they are not only ready to make use of Green IT. Green IT empowerment and social capital in the creative SMEs play an important function ingenerating of creativity and innovation in the Yogyakarta's creative SMEs. Creative industries which capitalize creative ideas and skills are expected to positively contribute to support the national economy. Practical implications: Creative SMEs grow and develop rapidly here and form clusters of creative industries in accordance with the resources of each cluster. Originality/value: This paper is a first attempt to overlook the significant role of green IT empowerment in SMEs' rapid development in Yogyakarta, a growing province in economic sector in Indonesia. The result of the study is expected to lead other similar research which in the future will craft out the role of economic development and the use of environmental friendly material of production.
Keywords: 650; empowerment of Green IT; social capital; creativity; innovation; environmental friendly